Structural and Functional Alterations in Visual Pathway After Optic Neuritis in MOG Antibody Disease: A Comparative Study With AQP4 Seropositive NMOSD - Gao, Chenyang; Zhuo, Zhizheng; Duan, Yunyun; Yao, Yajun; Su, Lei; Zhang, Xinghu; Song, Tian (Frontiers in Neurology, 2021)
Objective: Optic neuritis is an important clinical manifestation of neuromyelitis optic spectrum disease (NMOSD). Myelin Oligodendrocyte Glycoprotein (MOG) antibody-related and aquaporin 4 (AQP4) antibody-related optic neuritis show different disease patterns. The aim of this study was to explore the differences in structure and function of the visual pathway in patients with optic neuritis associated with MOG and AQP4 antibodies. Methods: In this prospective study, we recruited 53 subjects at Beijing Tiantan Hospital, including 12 with MOG Ig+ optic neuritis (MOG-ON), 13 with AQP4 Ig+ optic neuritis (AQP4-ON) and 28 healthy controls (HCs). Fractional anisotropy (FA) , mean diffusivity（MD）, axial diffusivity(AD) and radial diffusivity(RD), of optic radiation (OR), primary visual cortex volume (V1), brain volume and visual acuity (VA) were compared among groups. A multiple linear regression was used to explore associations between VA and predicted factors. In addition, we used optical coherence tomography (OCT) to examine thickness of the peripapillary retinal nerve fiber layer (pRNFL) and retinal ganglion cell complex (GCC) in a separate cohort consisting of 15 patients with optic neuritis (8 MOG-ON and 7 AQP4-ON) and 9 patients with non-optic neuritis (3 MOG-NON and 6 AQP4-NON). Results: Diffusion tensor imaging showed that the FA of OR was lower than controls in patients with AQP4-ON (p＜0.001) but not those with MOG-ON (p=0.063) and was significantly different between the latter two groups (p=0.021), while V1 was lower than controls both in MOG-ON (p=0.025) and AQP4-ON (p＜0.001). The VA outcomes were better in MOG-ON than AQP4-ON, and linear regression analysis revealed that VA in MOG-ON and AQP4-ON was both predicted by the FA of OR (standard β = -0.728 and -0.521, p = 0.006 and 0.034). Both patients of MOG-ON and AQP4-ON showed neuroaxonal damage in the form of pRNFL and GCC thinning but showed no statistically significant difference (p=0.496, 0.789). Conclusion: The Structural integrity of OR in patients with MOG-ON, which is different from the imaging manifestations of AQP4-ON, may be a reason for the better visual outcomes of patients with MOG-ON.